Inspired by 2012 : the legacy from the London 2012 Olympic and Paralympic Games : a joint UK Government and Mayor of London report.: the legacy from the London 2012 Olympic and Paralympic Games : a joint UK Government and Mayor of London report. (2016) - Unknown
No abstract available